Convergence of information networks as a sociocultural strategic innovation - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The influence of convergent technologies on social processes of Information society is analized. It is proved that social modernizationrequires an interpretation of convergence as a strategic innovation.